2015
DOI: 10.2131/fts.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration of perfluorinated compounds in wild medaka is related to octanol/water partition coefficient

Abstract: Perfluorinated compounds (PFCs) have been used widely, detected worldwide in the environment, and have accumulated highly in animals. As far as we know, there have been no reports which relate the PFC concentration in wild animals to the physicochemical properties. Therefore, we measured the concentrations of 15 currently available PFCs (perfluorocarboxylic acids with x carbons: Cx, perfluorosulfonic acids with x carbons: CxS) in medaka and the environmental water where medaka live. Samples were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
1
Order By: Relevance
“…The organ samples were minced thoroughly, and PFC concentrations in organ or blood samples of 0.2 g were measured. All samples were measured according to the method of our previous study (Iwabuchi et al, 2015). Briefly, the samples (except water) were weighed and put in 15 mL PP tube with 0.25 M sodium carbonate, then were added of MPFAC-MXA (containing 1 ng of each surrogate).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The organ samples were minced thoroughly, and PFC concentrations in organ or blood samples of 0.2 g were measured. All samples were measured according to the method of our previous study (Iwabuchi et al, 2015). Briefly, the samples (except water) were weighed and put in 15 mL PP tube with 0.25 M sodium carbonate, then were added of MPFAC-MXA (containing 1 ng of each surrogate).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to C8S or C8A, perfluorohexanoic acid (C6A) and perfluorononanoic acid (C9A) have been detected in the environment and in humans (Kannan et al, 2001;De Solla et al, 2012;Tsuda et al, 2012;Saito et al, 2013;Pérez et al, 2013;Ahrens et al, 2015;Iwabuchi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Each sandworm was spiked with native PFAC-MXA (1 ng and 10 ng each, respectively) and SUR (1 ng each). Pretreatment of sandworm samples followed a previously employed method for medaka extraction (Iwabuchi et al 2015) with modifications on using Presep PFC-II SPE cartridge. Sandworm sample was spiked with native PFAAs in 15 mL PP centrifuge tube.…”
Section: Sandworm Sample Preparation and Pfaa Extractionsmentioning
confidence: 99%
“…They have also been used to add stain-resisting properties to fabrics since 1950s. The long chained-PFAAs, such as perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS) are persistent and bio accumulative (Iwabuchi et al, 2015) and are detected in humans (Cariou et al, 2015). PFAAs are harmful to animals: neurotoxic-ity of perfluorooctane sulfonate (PFOS) in rats and mice after a single oral exposure (Sato et al, 2009) and after a sub chronic exposure (Kawamoto et al, 2011) is suggested to be underlined by its similar effect on membrane potential and increased intracellular Ca ++ shown in paramecium (Kawamoto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%